Phytochemical screening of some Euphorbiaceae members - V, Kothale K; P, Rothe S; N, Pawade P (Journal of Phytology, 2011)
The present investigation includes the Phytochemical screening of some medicinally important plants from the family Euphorbiaceae. All the members studied are exotic but naturalized except Ricinnus communis L. which is commercially cultivated in India. Plant extracts were prepared in various solvents and phytochemically they were tested in the solvent where the good extraction or active extraction observed, Phytochemical tests were carried out specially for screening secondary metabolites from the selected exotic medicinal plants from family Euphorbiaceae. Six genera and seven species of Euphorbiaceae were phytochemically analyzed to find secondary metabolites. <!--EndFragment--> Â 